Physiologic, health, and production responses of dairy cows supplemented with an immunomodulatory feed ingredient during the transition period - Brandao, A. P. [UNESP]; Cooke, R. F.; Corra, F. N. [UNESP]; Piccolo, M. B. [UNESP]; Gennari, R. [UNESP]; Leiva, T. [UNESP]; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2016)
This study compared physiological, health, and productive parameters in dairy cows supplemented or not with Omnigen-AF (OMN, Phibro Animal Health, Teaneck, NJ) during the transition period. Thirty-eight nonlactating, multiparous, pregnant Holstein x Gir cows were ranked by body weight (BW) and body condition score (BCS), and assigned to receive (in 19) or not (CON; n = 19) OMN at 56 g/cow daily (as-fed basis) beginning 35 d before expected date of calving. Before calving, cows were maintained in single drylot pen with ad libitum access to corn silage, and received (as-fed basis) 3 kg/cow daily of a concentrate. After calving, cows were moved to an adjacent drylot pen, milked twice daily, offered (as-fed basis) 35 kg/cow daily of corn silage, and individually received a concentrate formulated to meet their nutritional requirements after both milkings. Cows received OMN individually as top-dressing in the morning concentrate feeding. Before calving, cow BW and RCS were recorded weekly and blood samples were collected every 5 d beginning on d 35 relative to expected calving date. After calving and until 46 d in milk, BW and BCS were recorded weekly, individual milk production was recorded, and milk samples were collected daily for total solids and somatic cell count analyses. Blood was sampled daily from 0 to 7 d in milk, every other day from 9 to 21 d in milk, and every 5 d from 26 to 46 d in milk. On 30 and 46 d in milk, cows were evaluated for endometritis via cytobrush technique, based on % of polymorphonuclear (PMN) cells in 100 total cell count (PMN I endow trial cells). On 48.7 +/- 1.6 d in milk, 9 cows/treatment received a lipopolysaccharide (LPS) injection (0.25 mu g/kg of BW), and blood was sampled hourly from 2 to 8 h, at 12-h intervals from 12 to 72 h, and at 24-h intervals form 96 to 120 h relative to LPS administration. No treatment differences were detected on BW, BCS, serum concentrations of cortisol, fatty acids, insulin, glucose, haptoglobin, cortisol, and insulin-like growth factor-I. Cows receiving OMN had greater milk yield (30.3 vs. 27.1 kg/d) and percentage of PMN cells in endometrial cell population (12.2 vs. 3.9%) compared with CON cows. After LPS administration, cows receiving OMN had greater mean serum haptoglobin (212 vs. 94 mu g/mL), as well as greater serum concentration of tumor necrosis factor a at 1, 2, and 3 h relative to LPS injection compared with CON cows. In conclusion, OMN supplementation during the transition period enhanced innate immunity parameters and increased milk production in dairy cows.
Keywords: inflammation; milk production Omnigen-AF; transition cows